360 Intrusions in a Miniature Volcano: Birth, Growth, and Evolution of an Analog Edifice - Derrien, Allan; Taisne, Benoit (Frontiers in Earth Science, 2019)
Most volcanoes throughout the world have been monitored with geophysical data (seismology and geodesy) for no more than three decades, a relatively short time compared to their overall life. The consequence is that we lack a long observation of volcanic growth and behavior to get a more complete picture of the interaction between edifice stress state and magma transfer. Here we present the birth and evolution of a 83 x 83 cm analog model, where we reproduce for the first time volcanic growth over 360 successive intrusions (15 mL every half hour, at a rate of 3 mL/min) in an analog elasticity-dominated material (pigskin gelatine). By observing the development of this model volcano, we hope to provide insights to the study of long-term volcanic activity. In particular, we are interested in stress accumulation/release cycles and their role in the triggering of distant eruptions. Our model volcano started as a flat topography and ended 3.82 cm in height at the summit. It displayed cyclic eruptive patterns with alternating phases of eruptive and purely intrusive behavior. Alike to many intraplate volcanoes in nature, main dyke swarms produced in the experiment were disposed in a three-branched radial pattern centered above the injection source (“volcanic rift zones”). They were accompanied by two radial sill networks, at source depth and edifice base. Long-term radial compressive stress building during dyke swarming was likely compensated by radial compressive stress release during sill emplacement. Near-surface stresses, deduced from the main orientation eruptive fissures and “dry” fractures, became more localized as the volcano grew. At the end of the experiment, the shallow stress field was interpreted as generally extensional radial at the summit, extensional tangential on the flanks, and compressive radial in distal areas. This experiment showcases the potential of studying long-term stress permutations in volcanic edifices in the understanding of their morphology and successive activity phases.